Pengembangan Kemampuan Teknologi dengan Prodistik melalui Manajemen Madrasah - Maskur; Fathor Rahman (Yayasan Avicenna, 2022)
The approach used in this research is descriptive qualitative with a case study type. While the research location is at State Senior High School 2 Banyuwangi. Data collection techniques used include observation and in-depth interviews which are equipped with documentation. The data analysis technique refers to the Miles and Huberman technique which includes data reduction, data display, and data/conclusion verification. The results showed that Madrasah management in implementing PRODISTIK, namely collaborating with ITS Surabaya, forming IT and ToT Skills Vocational Teams, developing the PRODISTIK curriculum, as well as monitoring and evaluating programs in collaboration with ITS every semester. The implication is that educational institutions can realize the Madrasah program to the fullest if there is cooperation with other relevant institutions or institutions.